Acute Cervical Longitudinally Extensive Transverse Myelitis in a Child With Lipopolysaccharide-Responsive-Beige-Like-Anchor-Protein (LRBA) Deficiency: A New Complication of a Rare Disease - Chinello, Matteo; Mauro, Margherita; Cantalupo, Gaetano; Talenti, Giacomo; Mariotto, Sara; Balter, Rita; De Bortoli, Massimiliano; Vitale, Virginia; Zaccaron, Ada; Bonetti, Elisa; Di Carlo, Daniela; Barzaghi, Federica; et al. (Frontiers in Pediatrics, 2020)
Lipopolysaccharide responsive beige-like anchor protein (LRBA) deficiency is a primary immunodeficiency disorder (PID) that can cause a common variable immunodeficiency (CVID)-like disease. The typical features of the disease are autoimmunity, chronic diarrhea and hypogammaglobulinemia. Neurological complications are also reported in patients affected by LRBA deficiency. We describe a 7-year old female with an acute cervical longitudinally extensive transverse myelitis (LETM) as a feature of LRBA deficiency. This is the first case of LETM associated with LRBA deficiency described in literature.